Single-cell RNA landscape of osteoimmune microenvironment in osteoporotic vertebral compression fracture and Kümmell's disease - Xu, Yude; Huang, Suixiang; Li, Zhencong; Dai, Libing; Wu, Hao; Wang, Peigeng; Yao, Xiguan; Luo, Wei; Liu, Yiming; Yang, Weichao; Feng, Yi; Miao, Haixiong; et al. (Frontiers in Cell and Developmental Biology, 2023)
Background: Single-cell RNA sequencing (scRNA-seq) enables specific analysis of cell populations at single-cell resolution; however, there is still a lack of single-cell-level studies to characterize the dynamic and complex interactions between osteoporotic vertebral compression fractures (OVCFs) and Kümmell’s disease (KD) in the osteoimmune microenvironment. In this study, we used scRNA-seq analysis to investigate the osteoimmune microenvironment and cellular composition in OVCFs and KD. Methods: ScRNA-seq was used to perform analysis of fractured vertebral bone tissues from one OVCF and one KD patients, and a total of 8,741 single cells were captured for single-cell transcriptomic analysis. The cellularity of human vertebral bone tissue was further analyzed using uniform manifold approximation and projection. Pseudo-time analysis and gene enrichment analysis revealed the biological function of cell fate and its counterparts. CellphoneDB was used to identify the interactions between bone cells and immune cells in the osteoimmune microenvironment of human vertebral bone tissue and their potential functions. Results: A cellular profile of the osteoimmune microenvironment of human vertebral bone tissue was established, including mesenchymal stem cells (MSCs), pericytes, myofibroblasts, fibroblasts, chondrocytes, endothelial cells (ECs), granulocytes, monocytes, T cells, B cells, plasma cells, mast cells, and early erythrocytes. MSCs play an immunoregulatory function and mediate osteogenic differentiation and cell proliferation. The differentiation trajectory of osteoclasts in human vertebral bone tissue was also revealed. In addition, ECs actively participate in inflammatory infiltration and coupling with bone cells. T and B cells actively participate in regulating bone homeostasis. Finally, by identifying the interaction of ligand–receptor pairs, we found that immune cells and osteoclasts have bidirectional regulatory characteristics, have the effects of regulating bone resorption by osteoclasts and promoting bone formation, and are essential for bone homeostasis. It is also highlighted that CD8-TEM cells and osteoclasts might crosstalk via CD160–TNFRSF14 ligand–receptor interaction. Conclusion: Our analysis reveals a differential landscape of molecular pathways, population composition, and cell–cell interactions during OVCF development into KD. OVCFs exhibit a higher osteogenic differentiation capacity, owing to abundant immune cells. Conversely, KD results in greater bone resorption than bone formation due to depletion of MSCs and a relatively suppressed immune system, and this immune imbalance eventually leads to vertebral avascular necrosis. The site of action between immune cells and osteoclasts is expected to be a new therapeutic target, and these results may accelerate mechanistic and functional studies of osteoimmune cell types and specific gene action in vertebral avascular necrosis and pathological bone loss diseases, paving the way for drug discovery.